2012
DOI: 10.1021/jf303069v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Quantitative Structure–Activity Relationship (QSAR) Study of Novel Isoxazoline and Oxime Derivatives of Podophyllotoxin as Insecticidal Agents

Abstract: An ultrahigh-performance liquid chromatography (UHPLC) tandem mass spectrometric (MS/MS) method was developed for the simultaneous quantification of 2-acetyl-4-tetrahydroxybutylimidazole (THI), 2- and 4-methylimidazoles (2-MI and 4-MI), and 5-hydroxymethylfurfural (HMF) in beverage samples. A C30 reversed-phase column was used in this method, providing sufficient retention and total resolution for all targeted analytes, with an MS/MS instrument operated in selected reaction monitoring (SRM) mode for sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…For example, the corrected mortality rate of 5b against M. separata after 10 days was only 3.3%, after 20 days it had increased to 34.5%, and after 36 days to 55.2%. Meanwhile, the symptoms of M. separata treated by the tested compounds were also observed in the same way as in our previous works for podophyllotoxin derivatives [9][10][11]. The pupation of the larvae and the adult emergence of M. separata were inhibited by these compounds, therefore, the stage from the larvae to adulthood of M. separata was prolonged as compared with the control group.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…For example, the corrected mortality rate of 5b against M. separata after 10 days was only 3.3%, after 20 days it had increased to 34.5%, and after 36 days to 55.2%. Meanwhile, the symptoms of M. separata treated by the tested compounds were also observed in the same way as in our previous works for podophyllotoxin derivatives [9][10][11]. The pupation of the larvae and the adult emergence of M. separata were inhibited by these compounds, therefore, the stage from the larvae to adulthood of M. separata was prolonged as compared with the control group.…”
Section: Resultssupporting
confidence: 68%
“…The insecticidal activity of compounds 1-3 and 5a-m against the prethird-instar larvae of M. separata was assessed by the leaf-dipping method as described previously [10]. For each compound, 30 larvae Brought to you by | Freie Universität Berlin Authenticated Download Date | 7/1/15 3:14 PM (ten larvae per group) were used.…”
Section: Insecticidal Assay Of 1-3 and 5a-mmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Additionally, Hu et al found that once a 36 chlorine atom was introduced at the C-2' position of podophyllotoxin derivatives, the 37 corresponding compounds showed no significant cytotoxicity. 17 More recently, we have 38 prepared a series of oxime sulfonate derivatives of picropodophyllotoxin 18 (2, Figure 1) and 39 4α/β-acyloxy-2′(2′,6′)-(di)halogenopodophyllotoxin derivatives 19,20 (3, Figure 1) as 40 insecticidal agents, and found some derivatives exhibited more potent insecticidal activity 41 than toosendanin, a commercial botanical insecticide isolated from Melia azedarach. Where T is the mortality rate in the tested compounds group, and C is the mortality rate in the 210 blank control group (T and C were expressed as percentages).…”
Section: Introduction 23mentioning
confidence: 99%
“…[16][17][18][19] Interestingly, a similar strategy had already been successfully applied in the synthesis of rapamycin derivativezotarolimus, 20) an anti-proliferative drug, which modified by replacement of hydroxyl with tetrazole at C-43 postion. Intrigued by the above observation, using a similar design as zotarolimus, we plan to replace the tetrazole moiety of zotarolimus with benzothiazole group by means of structure-based bioisosterism, 21,22) both of them with the same heterocyclic backbone.…”
mentioning
confidence: 99%